Changes in individual indicators of protein metabolism in experimental pnevmonia in a imobilizatsiynoho stress and correction corvitin - Ferents, Nataliya M. (Journal of Education, Health and Sport, 2015)
Ferents N M. Зміни окремих показників білкового обміну при експериментальній пневмонії в умовах іммобілізаційного стресу та їх корекція Корвітином = Changes in individual indicators of protein metabolism in experimental pnevmonia in a imobilizatsiynoho stress and correction Corvitin. Journal of Education, Health and Sport. 2015;5(2):141-148. ISSN 2391-8306. DOI: 10.5281/zenodo.15710 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A141-148 https://pbn.nauka.gov.pl/works/541747 http://dx.doi.org/10.5281/zenodo.15710 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. УДК 61624 – 002 -036.11 – 092:612.018 ЗМІНИ ОКРЕМИХ ПОКАЗНИКІВ БІЛКОВОГО ОБМІНУ ПРИ ЕКСПЕРИМЕНТАЛЬНІЙ ПНЕВМОНІЇ В УМОВАХ ІММОБІЛІЗАЦІЙНОГО СТРЕСУ ТА ЇХ КОРЕКЦІЯ КОРВІТИНОМ CHANGES IN INDIVIDUAL INDICATORS OF PROTEIN METABOLISM IN EXPERIMENTAL PNEVMONIA IN A IMOBILIZATSIYNOHO STRESS AND CORRECTION CORVITIN Н. М. Ференц N M Ferents Львівський національний медичний університет імені Данила Галицького Lviv National Medical University Daniel Galician Реферат Изучение сдвигов отдельных показателей белкового обмена, в частности белка, альбуминов, глобулиновых фракций при экспериментальной пневмонии в условиях иммобилизацийного стресса, и их коррекция с помощью корвитина, даёт основание утверждать, что этот антиоксидант оказывает положительное влияние, которое особенно хорошо видно по повышением содержания в плазме крови альбуминов и снижение уровня глобулинов в условиях его применения. Ключевые слова: белковый обмен, пневмония, иммобилизационный стресс, Корвитин. Abstract Study of changes of selected indicators of protein metabolism, including protein, albumin, globulin fractions in experimental pneumonia in aimobilizatsiynoho stress, and their correction using Corvitin gives reason to believe that this antioxidant reveals positive effect, which is particularly well illustrated by the increasing of plasma blood albumin and globulin by reducing conditions of use. Keywords: protein metabolism, pneumonia, immobilization stress, Corvitin.